SOCIAL RESPONSIBILITY OF UKRAINIAN PRIVATE ENTERPRISES: MODERN APPROACHES - HRACHOVA, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is the analysis of modern approaches to the social responsibility of enterprises, as well as the determination of ways to optimize scientific research taking into account the latest scientific developments and the realities of Ukrainian society. To achieve the goal, the following tasks were solved: the contribution of domestic authors to the improvement of the theoretical basis of social responsibility was investigated; the contribution of scientists to the development of the analytical basis for assessing the social responsibility of enterprises was investigated; modern directions of improvement of social responsibility and their compliance with the peculiarities of social processes taking place in Ukraine are studied. The main method of obtaining information was the analysis of documents, namely dissertations defended over the past 10 years. The analysis of documentary sources showed that the improvement of the theoretical basis of social responsibility is mainly carried out by scientists due to clarification of the essence of the concept of "social соціальна відповідальність responsibility". The development of the analytical basis for assessing social responsibility mainly consists in substantiating the list of indicators (or indicators) for assessing the current state of social responsibility, calculating the integral indicator, and developing recommendations for improving information support for assessing social responsibility (developing reporting forms or improving existing reporting forms). To modern directions of improvement of social responsibility, formation of system, strategy, mechanism of social responsibilityBased on the results of the analysis of the dissertations, conclusions were made about the directions of further research on social responsibility, in particular with the aim of improving the theoretical basis of social responsibility - to develop a terminological system of research; in order to develop the analytical basis - to improve methodological approaches to the analysis of social responsibility by determining the motivating and demotivating factors of the implementation of social responsibility of business, which vary depending on the political, economic, social, technological, legal and environmental aspects of the external environment; applied developments (formation of a system, strategy, mechanism of social responsibility, etc.) should take into account the peculiarities of social processes taking place in Ukraine.
Keywords: social responsibility; private enterprises; social development; analysis of documents; theoretical basis of social responsibility; analytical basis of social responsibility